Electrochemical Solution of Molybdenum Mixture - Ziyadullaev Abdukakhhar Shamsievich; Suyarov Zainiddin Holbutaevich; Abdulkhamidov Shukhratjon Akhmadjonovich; Pulatov Ilhom Mamadaminovych; Yernazarov Umid Nurillaevich (Genius Journals, 2023)
When molybdenum is processed by powder metallurgy, insoluble molybdenum compounds arise, which form specs on the surface of nickel boats (Ni - 63%, Mo - 27% alloy). It is necessary to search for an effective technology for cleaning nickel boats from molybdenum cake, ensuring their repeated use and return to the production cycle of metal bound in the cake
Keywords: molibden; electrochemical solution; molibden mixture